Dynamisme linguistique (amazigh-arabe/ anglais-français) dans l’entreprise agroalimentaire - Cevital - en Algérie - Imene Lainseur; Mourad Bektache (Multilinguales)
This research examines the relationship between languages and the economic sector. It is part of sociolinguistic study carried out within the agri-food company Cevital of Bejaia. This disciplinary field demonstrates the importance of languages in companies. The article develops among other things, adequate strategies to manage their linguistic component. Languages convey various social representations in the company. In this article, we are interested in the place given to national languages (Amazigh and Arabic) as well as foreign languages (French and English) within Algerian companies. It is to identify the choices made at Cevital in terms of languages and their uses communication situations (formal and informal) in order to contribute to the smooth running of professional activities.